2022
DOI: 10.3389/fimmu.2022.790334
|View full text |Cite
|
Sign up to set email alerts
|

Pre-COVID-19 Immunity to Common Cold Human Coronaviruses Induces a Recall-Type IgG Response to SARS-CoV-2 Antigens Without Cross-Neutralisation

Abstract: The capacity of pre-existing immunity to human common coronaviruses (HCoV) to cross-protect against de novo COVID-19is yet unknown. In this work, we studied the sera of 175 COVID-19 patients, 76 healthy donors and 3 intravenous immunoglobulins (IVIG) batches. We found that most COVID-19 patients developed anti-SARS-CoV-2 IgG antibodies before IgM. Moreover, the capacity of their IgGs to react to beta-HCoV, was present in the early sera of most patients before the appearance of anti-SARS-CoV-2 IgG. This implied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The presence of IgM and IgA antibodies without IgG in 13.6% of our samples is likely the result of cross-reactivity in our assays with seasonal coronavirus strains. 22,23 Our finding that most seropositive participants exhibited IgG antibodies alone suggests that they had likely contracted SARS-CoV-2 weeks, if not months, before the study.…”
Section: Discussionmentioning
confidence: 89%
“…The presence of IgM and IgA antibodies without IgG in 13.6% of our samples is likely the result of cross-reactivity in our assays with seasonal coronavirus strains. 22,23 Our finding that most seropositive participants exhibited IgG antibodies alone suggests that they had likely contracted SARS-CoV-2 weeks, if not months, before the study.…”
Section: Discussionmentioning
confidence: 89%
“…29 Several other studies have also reported the presence of cross-reactive antibodies in naïve or pre-COVID samples. [30][31][32][33] While several studies have assessed antibody variations in HCWs, few have investigated the association of sociodemographic factors. In a 10-month study of HCWs, IgG response was detected up to 10 months postvaccination.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study identified a total of 15 such SARS‐CoV‐2 spike protein epitopes that cross‐react with antibodies generated against various acute and chronic viral antigens 29 . Several other studies have also reported the presence of cross‐reactive antibodies in naïve or pre‐COVID samples 30–33 …”
Section: Discussionmentioning
confidence: 99%
“…Some data showed that the pre-existing antibodies response in un-infected populations, especially in children and teenagers exhibited specific neutralizing activity against SARS-CoV-2 ( 14 ), and high levels of pre-existing immune responses against LPH-CoVs were associated with mitigating the disease severity of coronavirus disease 2019 (COVID-19) ( 15 17 ) or reduced the duration of symptom ( 18 ). Yet, other studies suggested a lack of SARS-CoV-2 cross-neutralization activity although antigen-specific antibodies response was detected from pre-pandemic serum samples of SARS-CoV-2 ( 11 , 19 , 20 ). These conclusions vary greatly in different cohorts which commonly include adults, and the cross-reactive antibodies against SRAS-CoV-2 in children with pre-existing LPH-CoVs humoral immunity need to be elucidated.…”
Section: Introductionmentioning
confidence: 95%